KOMUNITAS DIATOM PADA EKOSISTEM MANGROVE PANTAI UTARA JAWA TENGAH - R. Soeprobowati, Tri Retnaningsih; W.A. Suedy, Sri (JURNAL SAINS DAN MATEMATIKA, 2010)
Diatom is a unique microalgae, undoubtly good bioindicator of water quality, andable to be usedf or paleoreconstructione nvironmentacl hangesI.t s relatedt o the silicious frustule,t hat remainpreserved in the sediment. Diatom have widespread distribution, including in the mangrove ecosystem.Mangroveâ‚¬ cosystema lso unique, influenceb y freshwatera nd salinew ater, therefore,t he biodiversity in themangrovee cosystema re very high. However,t he sharpd egradationo f mangrovee cosystemin the NorthernCoast of Central might reduce the biodiversity, particularly diatom. This research is conducted in order tostudy the diatom community vertically in the Norther Coast of Central Java and their correlation with waterquallty. From 54 sediments amples, 147 diatoms speciesw are identified, 10.88% of Centrophycidaea nd89.12o/o of PennatophycidaeP. lanktonic and benthonic ( epifitic, epilitic and epipelic) diatoms werecomposed iatoms community in the mangrovee cosystemF. reshwaterd iatom have an important role in themangreovee cosystemi,n dicatedb y the dominanceo f freshwaterd iatOmsin all sites.permalink : http://ejournal.undip.ac.id/index.php/sm/article/view/2850